Intumescent fire-retardant acrylic coatings : effects of additive loading ratio and scale of testing - Ng, Yan Hao (2022)
This work explores the importance of varying the ratio of conventional flame-retardant additives and the scale of testing on the thermal and flammability/fire performance of acrylic-based coatings. Ammonium polyphosphate (APP), pentaerythritol (PER), and expandable graphite (EG) are used as intumescent additives by varying their ratios as 1:1:3 or 1:3:1 or 3:1:1. APP, PER and EG are used as acid source, carbonising agent and blowing agent, respectively. Despite the different roles of APP, PER, and EG, in all the compositions, the physical mechanism of exfoliation of graphite played an important role in offering the fire protection. With higher loadings of EG, the fire-resistance time was higher. However, there were clear differences in the protection extent when tested in a furnace under one-dimensional heat transfer conditions (bench-scale) as opposed to three-dimensional large-scale testing. Parameters that are not intrinsic to the coating system like char cohesion, cracking, delamination from the substrate, rapid and non-directional expansion, and even higher heat fluxes experienced by the edges of the I steel section affect the fire performance.